2011
DOI: 10.1016/j.actamat.2011.02.021
|View full text |Cite
|
Sign up to set email alerts
|

The equilibrium crystal shape of nickel

Abstract: The crystal shape of Ni particles, dewetted in the solid state on sapphire substrates, was examined as a function of the partial pressure of oxygen (P(O2)) and iron content using scanning and transmission electron microscopy. The chemical composition of the surface was characterized by atom-probe tomography. Unlike other FCC equilibrium crystal shapes, the Ni crystals containing little or no impurities exhibited a facetted shape, indicating large surface anisotropy. In addition to the {111}, {100} and {110} fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 34 publications
8
35
0
Order By: Relevance
“…This observation is in good agreement with previous results reported in the literature [21,38,39]. Recently Meltzman and co-workers [40] have shown that {1 0 0} facets are evident for the equilibrium shape of Ni nanoparticles while {2 1 1} facets are absent. The film was only annealed for a relatively short period of time during the in situ TEM experiments, and the presence of the {2 1 1} facets therefore suggest that the corresponding nickel islands have not yet fully reached thermodynamic equilibrium.…”
Section: In Situ Annealingsupporting
confidence: 83%
See 1 more Smart Citation
“…This observation is in good agreement with previous results reported in the literature [21,38,39]. Recently Meltzman and co-workers [40] have shown that {1 0 0} facets are evident for the equilibrium shape of Ni nanoparticles while {2 1 1} facets are absent. The film was only annealed for a relatively short period of time during the in situ TEM experiments, and the presence of the {2 1 1} facets therefore suggest that the corresponding nickel islands have not yet fully reached thermodynamic equilibrium.…”
Section: In Situ Annealingsupporting
confidence: 83%
“…The film was only annealed for a relatively short period of time during the in situ TEM experiments, and the presence of the {2 1 1} facets therefore suggest that the corresponding nickel islands have not yet fully reached thermodynamic equilibrium. However, the thickness of the TEM sample and the presence of NiO on the surface of the metal film may cause a change in the equilibrium shape of the Ni islands [40]. The dispersed Ni islands for the annealed 5 nm film show rounded edges, with no facet formation.…”
Section: In Situ Annealingmentioning
confidence: 99%
“…By far 15 the best experimental approach consists of analysis of carefully equilibrated crystallites [1,2,3]. Such process is viable on some materials but not the others, and can be questionable in reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the large technological importance of this system, Ni-alumina interfaces were not experimentally studied to the same extent as other metalalumina interfaces. This is perhaps due to the relatively high melting temperature and/or because of the relatively large surface energy of Ni, which requires an extremely pure environment for model studies [8][9].Given the importance of the Ni-Al 2 O 3 system, and the questions raised by numerous atomistic simulations of this system, the goal of the present work is to determine the structure and energy of Ni equilibrated in contact with (0001) sapphire. Samples are based on very pure thin Ni films which were dewetted in the solid-state (and under controlled impurity levels and oxygen partial pressure) to reach equilibrium, from which both the interface structure and energy can be determined.…”
mentioning
confidence: 99%
“…In contrast to the large technological importance of this system, Ni-alumina interfaces were not experimentally studied to the same extent as other metalalumina interfaces. This is perhaps due to the relatively high melting temperature and/or because of the relatively large surface energy of Ni, which requires an extremely pure environment for model studies [8][9].…”
mentioning
confidence: 99%